P153 CHALLENGES IN MINIMALLY INVASIVE REPAIR OF ILEAL CONDUIT PARASTOMAL HERNIAS. (25th November 2021) - Dewulf, Maxime; Pletinckx, Pieter; Nachtergaele, Femke; Muysoms, Filip
Abstract: Aim: Parastomal hernia after radical cystectomy and ileal conduit urinary diversion is an underestimated and probably undertreated condition with significant impact on quality of life. However, its surgical treatment is challenging and prone to recurrence and complications. Literature on the subject is scarce and of poor quality, and the optimal surgical treatment of this condition remains to be determined. Material and Methods: In this retrospective patient series, a prospectively maintained database was screened. Data from all patients undergoing surgical treatment for a parastomal hernia after cystectomy and ileal conduit urinary diversion in our center were collected. The incidence of local recurrence was defined as primary endpoint. The rate of in-hospital complications was defined as secondary endpoint. Results: Between May 2016 and June 2020, 15 patients underwent minimally invasive repair of a parastomal hernia of an ileal conduit at our center. Almost half of the patients had a concomitant midline incisional hernia (7/15; 46, 7%). The majority of patients were treated with robotic-assisted laparoscopic surgery (10/15; 66, 7%). Median follow-up was 366 days. One patient developed a local recurrence of her parastomal hernia on day 66 postoperatively, this recurrence was treated with intraperitoneal mesh. Conclusions: The minimally invasive surgical treatment of a parastomal hernia after ileal conduit urinary diversion poses specific perioperative challenges that require a broad surgical armamentarium and a tailored approach. This paper confirms the significant morbidity after this type of surgery and proposes a flow chart to standardize the choice of surgical technique, depending on the presence of a concomitant midline incisional hernia and perioperative findings.